Integrasi Usaha Tanaman Pangan dan Sapi Potong Serta Analisis Keuangannya pada Petani Transmigran di Bengkulu Tengah (BUSINESS INTEGRATION OF FOOD CROPS AND BEEF CATTLE AND ITS FINANCIAL ANALYSIS OF TRANS MIGRANTS FARMERS IN CENTRAL BENGKULU) - Rusdiana, Supardi; Sutedi, Endang; Adiati, Umi; Kusumaningrum, Diana Andrianita (Jurnal Veteriner; Vol 20 No 1 (2019)DO - 10.19087/jveteriner.2019.20.1.74, 2019)
The purpose of this study was to evaluate the financial value of food crops and beef cattle integrated farming trans migrants in Central Bengkulu. The research was carried out in Margo Mulyo Village, Pondok Kubang Sub-district, and Central Bengkulu Regency of Bengkulu Province from year 2017 to May 2018, by applying survey methodology. Secondary data were obtained from Department of Agriculture, Livestock and Plantation of Central Bengkulu  Regency and the primary data were gathered from respondents by purposive random sampling as many as 20 trans migrant farmers. Data were analyzed descriptively and economic analysis of business feasibility. The result of the research showed that the absorption of labor trans migrant farmers about 154.22 man days/ ha, corn cultivation business about 154.22 man days/ha and business livestock beef cattle around 139.4 man days/ha. Rice cultivation which expended by IDR 5,314,740,-/harvest, yielded net profit of IDR 4,938,495,-/harvest with B/C ratio of 0.96±0.23 Corn cultivation which expended by IDR 5,260,650,-/harvest, yielded net profit by IDR 1,100,600,-/harvest with B/C ratio of 0.24±0.09. Whilst beef cattle keeping, which expended of IDR 47,200,500,-/year, yielded net profit of IDR 5,902,500,-/ year with B/C ratio 0.14±.0.07 Integrated farming of food crops and cattle was financially beneficial.